Lignin-based magnetic super solid acid as well as preparation method and application thereof

By carboxylation, magnetic material composite and sulfonication modification of lignin, lignin-based magnetic super-strong solid acid is prepared, which solves the problems of difficulty in recycling lignin catalysts and product separation in the prior art, and achieves efficient preparation and wide application of solid acids.

CN119552382APending Publication Date: 2025-03-04DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311137792.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has difficulty in efficiently using lignin as a catalyst, especially in the recovery of catalysts and product separation, and no heterogeneous lignin-based solid acid materials with magnetic characteristics and super acidic positions have been seen.

Method used

By carboxylation modification, magnetic material composite and sulfonication modification of lignin, lignin-based magnetic super-strong solid acid was prepared. The method includes reacting lignin with an alkaline substance and a carboxylation reagent to form a carboxylated lignin, then reacting with a magnetic material precursor and hydrazine, and finally reacting with a sulfonating reagent to obtain a solid acid with magnetic and super acidic positions.

Benefits of technology

The preparation of lignin-based magnetic super-strong solid acid is achieved, with stable structure, easy recycling and widely used in the dehydration reaction of biomass nanomaterials and sugars. It has simple process, low cost, small environmental pollution, and has the prospect of industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552382A_ABST
    Figure CN119552382A_ABST
Patent Text Reader

Abstract

The invention discloses lignin-based magnetic super solid acid and a preparation method thereof. The preparation method at least comprises the following steps: (1) taking industrial lignin as a raw material, and introducing carboxylic acid groups to the surface of the industrial lignin; (2) compounding ferroferric oxide and a lignin matrix through a reduction reaction; and (3) finally introducing a benzenesulfonic acid group into the surface of the composite catalyst. The solid acid catalyst finally obtained in the invention retains excellent thermal stability of lignin, and has good recoverability and super acidic site. Moreover, the catalyst is made of biomass renewable materials, is low in manufacturing cost and small in environmental pollution, can be widely applied to acid catalytic reaction, and has industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a lignin-based magnetic super-strong solid acid and a preparation method and application thereof, belonging to the field of biomass catalytic materials. Background Art

[0002] Lignin is the main component of biomass and the most abundant renewable aromatic polymer on earth. It is a three-dimensional network polymer composed of phenylpropane structural units connected by different forms of carbon-carbon bonds and carbon-oxygen bonds. However, due to the complex and disordered structure of lignin itself and the cross-covalent connection between lignin and other components of the fiber cell wall, it has caused many challenges and difficulties in the current development and utilization of lignocellulose.

[0003] After hundreds of millions of years of evolution, lignin in plants has natural resistance to degradation and good thermal stability, making it an ideal raw material for catalyst preparation. In the past, sulfonate lignin, a product of the papermaking industry, was used as a homogeneous solid acid, but this caused great difficulties for the subsequent catalyst recovery and product separation. The surface of lignin is rich in hydroxyl functional groups, and a series of functional modifications can be performed to prepare heterogeneous recyclable magnetic super-strong solid acids. So far, there have been no reports on the synthesis of heterogeneous lignin-based solid acid materials with magnetic characteristics and super-strong acidic sites. Summary of the invention

[0004] According to one aspect of the present application, a lignin-based magnetic super solid acid is provided, wherein the lignin-based magnetic super solid acid is obtained by carboxylation modification of lignin, composite with magnetic materials and sulfonation modification.

[0005] The acidic site content of the lignin-based magnetic super-strong solid acid is 0.5-2 mmol / g.

[0006] According to another aspect of the present application, a method for preparing the above-mentioned lignin-based magnetic super-strong solid acid is provided, comprising the following steps:

[0007] (1) mixing lignin, an alkaline substance, a carboxylation agent, and water, and performing reaction I to obtain carboxylated lignin;

[0008] (2) mixing the carboxylated lignin obtained in (1), the magnetic material precursor, hydrazine, and water, and performing reaction II to obtain a composite material;

[0009] (3) The composite material obtained in (2), a sulfonating agent, an alcohol and water are mixed to perform reaction III to obtain the lignin-based magnetic super-strong solid acid.

[0010] (1)

[0011] The lignin is selected from at least one of alkali lignin, kraft lignin, enzymatic lignin, and organic solvent lignin;

[0012] The alkaline substance is selected from at least one of sodium hydroxide, calcium hydroxide, sodium carbonate and sodium bicarbonate;

[0013] The carboxylation agent is selected from sodium chloroacetate, sodium chloropropionate, 2,2,6,6-tetramethylpiperidine-1-oxide, etc.

[0014] The mass of the alkaline substance is 1 to 5 wt% of the mass of the lignin;

[0015] The molar ratio of the alkaline substance to the carboxylation agent is 1:1 to 3;

[0016] The solid-liquid ratio of the lignin to the water is 1:4-10 g / ml.

[0017] The temperature of the reaction I is 60-80°C;

[0018] The reaction time is 2 to 4 hours.

[0019] (2)

[0020] The magnetic material precursor is selected from at least one of ferric chloride and ferrous chloride;

[0021] The solid-liquid ratio of the carboxylated lignin to the water is 1:100-125 g / ml;

[0022] The usage ratio of the carboxylated lignin to the magnetic material precursor is 99-199:1;

[0023] The usage ratio of the hydrazine to the carboxylated lignin is 1 to 10 wt %.

[0024] The temperature of the reaction II is 60-90°C;

[0025] The time of the reaction II is 2 to 6 hours.

[0026] (3)

[0027] The sulfonating agent is selected from 4-diazobenzenesulfonate, 70% concentrated sulfuric acid, etc.

[0028] The alcohol is selected from ethanol;

[0029] The volume ratio of the water to the alcohol is 1:10-20;

[0030] The mass ratio of the sulfonating agent to the composite material is 10:1 to 5:2;

[0031] The ratio of the total mass of the sulfonating agent and the composite material to the total volume of the alcohol and the water is 1:10-100 g / ml.

[0032] The temperature of the reaction III is 50-80°C;

[0033] The time of the reaction III is 2-6 hours.

[0034] Specifically,

[0035] Step 1: Soak the industrial lignin in 80°C water and stir for 1 hour, then perform solid-liquid separation to remove residual chemicals and ensure efficient subsequent reactions;

[0036] Step 2: The dried and cleaned lignin solid is subjected to a series of modifications to finally achieve magnetism and super acidity. The specific process technology is as follows:

[0037] (1) Carboxymethylation modification

[0038] The purpose of this process is to enhance the acid sites provided by the lignin surface and strengthen the chelation with metal ions. First, lignin is mixed with deionized water at a certain solid-liquid ratio, and after adding an alkali agent, it is stirred at room temperature for 1 hour until it is completely dissolved; then the temperature is raised, a certain amount of sodium chloroacetate is added and reacted for several hours, among which temperature, time and amount of sodium chloroacetate are key parameters for controlling the degree of substitution. After the reaction is completed, water is added to dilute the system, and the system is adjusted to acidity with a dilute hydrochloric acid solution; the acid precipitated lignin is collected. Finally, the product is dried and ground to obtain carboxylated lignin.

[0039] Reaction process parameters:

[0040] Solid-liquid ratio: 1:4~1:10g / ml,

[0041] Alkali dosage: 1-5% (relative to absolute dry lignin),

[0042] The molar ratio of alkali agent to sodium chloroacetate: 1:1-1:3,

[0043] Reaction temperature: 60~80℃,

[0044] Reaction time: 2 to 4 hours,

[0045] (2) Lignin / Fe2O3 magnetic composite materials

[0046] After dispersing carboxymethylated lignin in deionized water at a certain solid-liquid ratio and ultrasonicating for 30-60 minutes, the pH value of the solution is adjusted to 9-10 with a 30% ammonia solution to completely dissolve the lignin; then a certain total amount of FeCl3·6H2O and FeCl2·4H2O is dissolved in water at a molar ratio of 2:1, and the Fe3+ / Fe2+ salt solution is slowly added to the lignin alkaline solution and stirred continuously; then the system is heated to 80°C, and a certain amount of 80% hydrazine hydrate is slowly added, and after stirring and reacting for 4 hours, the resulting black solution is cooled to room temperature; after adjusting the pH of the solution to acidity with a dilute hydrochloric acid solution, the precipitated solid is filtered, washed, dried, and ground to obtain a lignin / Fe2O3 magnetic composite material;

[0047] Reaction process parameters:

[0048] Liquid-solid ratio: 1:100-1:250g / ml,

[0049] Total amount of FeCl3·6H2O and FeCl2·4H2O: 20-50% (relative to absolute dry carboxymethylated lignin),

[0050] Molar ratio between hydrazine hydrate and Fe atoms in the system: 1:1-1:3

[0051] (3) Sulfonation

[0052] The obtained lignin / Fe2O3 magnetic composite material is dispersed in a mixed solution system of ethanol and water; then 4-diazobenzenesulfonate is added, the temperature is controlled, and the reaction is stirred for a certain time; the separated product is washed with deionized water until the pH value is about 6 to ensure that there is no free acid in the structure, and then dried to finally obtain a magnetic super-strong solid acid;

[0053] Reaction process parameters:

[0054] Solid-liquid ratio: 1:10-1:100g / ml,

[0055] The volume ratio of water to ethanol: 1:10-1:20,

[0056] The mass ratio of 4-diazobenzenesulfonate to lignin / Fe2O3 magnetic composite material is 10:1-5:2.

[0057] Reaction temperature: 50-80°C,

[0058] Reaction time: 2-4h,

[0059] Step 3: Characterize various properties and evaluate the reaction activity of the obtained magnetic superstrong solid acid.

[0060] According to another aspect of the present application, an application of the above-mentioned lignin-based super-strong magnetic solid acid is provided, which can be quickly separated, recovered and reused by a magnet.

[0061] The beneficial effects of this application include:

[0062] 1) The magnetic super-strong solid acid of the present invention has a stable structure, can undergo heterogeneous reactions, and is easy to recycle.

[0063] 2) The magnetic super-strong solid acid of the present invention can be applied to the preparation of various biomass nanomaterials and sugar dehydration reactions.

[0064] 3) The preparation method of the present invention is simple, low in cost, uses environmentally friendly raw materials, has little environmental pollution, and has a prospect for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 The process flow chart of the lignin-based magnetic super-strong solid acid is shown in FIG.

[0066] Figure 2 This is the appearance of the lignin-based super-strong magnetic solid acid obtained in Example 1;

[0067] Figure 3 This is the FTIR test graph of the lignin-based magnetic super solid acid obtained in Example 1. DETAILED DESCRIPTION

[0068] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0069] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0070] Depend on Figure 1 The process of preparing a magnetic super-strong solid acid using alkaline lignin as raw material includes: 1) cleaning and removing impurities; 2) carboxymethylation; 3) lignin / Fe2O3 magnetic composite material; 4) sulfonation, and the specific operations are as follows:

[0071] 1) Cleaning and removing impurities

[0072] In this implementation case, kraft lignin from a pulp mill in Hunan was selected and immersed in 80°C water and stirred for 1 hour before solid-liquid separation and drying.

[0073] 2) Carboxymethylation

[0074] After mixing 10g of lignin with 100ml of deionized water, add 0.5g of sodium hydroxide and stir at room temperature for 1 hour until it is completely dissolved; then heat to 80°C, add 1.46g of sodium chloroacetate and react for 4 hours; after the reaction, add 200ml of water to dilute the system, and adjust the system to acidity with a dilute hydrochloric acid solution; collect the acid-precipitated lignin, dry and grind the product to obtain carboxylated lignin.

[0075] 3) Lignin / Fe2O3 magnetic composite material

[0076] 10 g of carboxymethylated lignin was dispersed in 250 ml of deionized water and ultrasonicated for 30 minutes. The pH value of the solution was adjusted to 9–10 with 30% ammonia solution to completely dissolve the lignin. Then 2 g of FeCl3·6H2O and 0.79 g of FeCl2·4H2O were dissolved in water. 3+ / Fe 2+ The salt solution is slowly added to the lignin alkaline solution and stirred continuously; then the system is heated to 80°C, and 2.38g of 80% hydrazine hydrate is slowly added, and after stirring and reacting for 4 hours, the resulting black solution is cooled to room temperature; the pH of the solution is adjusted to acidity with a dilute hydrochloric acid solution, and the precipitated solid is filtered, washed, dried, and ground to obtain a lignin / Fe2O3 magnetic composite material;

[0077] 4) Sulfonation

[0078] The obtained 10g lignin / Fe2O3 magnetic composite material is dispersed in a mixed solution system of 100ml ethanol and 10ml water; then 1g 4-diazobenzenesulfonate is added, the temperature is controlled at 80°C, and the reaction is stirred for 2 hours; the separated product is washed with deionized water until the pH value is about 6 to ensure that there is no free acid in the structure, and then dried to finally obtain a magnetic super solid acid.

[0079] Figure 2 This is the appearance of the lignin-based super-strong magnetic solid acid obtained in Example 1;

[0080] Figure 3 This is the FTIR test graph of the lignin-based magnetic super-strong solid acid obtained in Example 1. It can be seen from the figure that the C=O corresponding to the carboxyl group of the modified lignin is at 1725-1700 cm -1 The stretching vibration peak at 1100 cm-1 of the sulfonic acid group appears first and then increases significantly. -1 The characteristic peaks also appear and are very strong.

[0081] Example 2

[0082] Depend on Figure 1The process of preparing a magnetic super-strong solid acid using organic solvent lignin as raw material includes: 1) cleaning and removing impurities; 2) carboxymethylation; 3) lignin / Fe2O3 magnetic composite material; 4) sulfonation, and the specific operations are as follows:

[0083] 1) Cleaning and removing impurities

[0084] In this implementation case, homemade softwood organic solvent lignin obtained by using ethanol was selected, and after being immersed in 80°C water and stirred for 1 hour, solid-liquid separation and drying were performed.

[0085] 2) Carboxymethylation

[0086] After mixing 100g of lignin with 1000ml of deionized water, add 5g of sodium hydroxide and stir at room temperature for 1 hour until it is completely dissolved; then heat to 80°C, add 14.6g of sodium chloroacetate and react for 4 hours; after the reaction, add 2000ml of water to dilute the system, and adjust the system to acidity with a dilute hydrochloric acid solution; collect the acid-precipitated lignin, dry and grind the product to obtain carboxylated lignin.

[0087] 3) Lignin / Fe2O3 magnetic composite material

[0088] 100 g of carboxymethylated lignin was dispersed in 2500 ml of deionized water and ultrasonicated for 30 minutes. The pH value of the solution was adjusted to 9–10 with 30% ammonia solution to completely dissolve the lignin. Then, 20 g of FeCl3·6H2O and 7.9 g of FeCl2·4H2O were dissolved in water at a molar ratio of 2:1. 3+ / Fe 2+ The salt solution is slowly added to the lignin alkaline solution and stirred continuously; the system is then heated to 80°C, and 23.8 g of 80% hydrazine hydrate is slowly added, and after stirring and reacting for 4 hours, the resulting black solution is cooled to room temperature; the pH of the solution is adjusted to acidity with a dilute hydrochloric acid solution, and the precipitated solid is filtered, washed, dried, and ground to obtain a lignin / Fe2O3 magnetic composite material;

[0089] 4) Sulfonation

[0090] The obtained 100g lignin / Fe2O3 magnetic composite material is dispersed in a mixed solution system of 1000ml ethanol and 100ml water; then 10g 4-diazobenzenesulfonate is added, the temperature is controlled at 80°C, and the reaction is stirred for 4 hours; the separated product is washed with deionized water until the pH value is about 6 to ensure that there is no free acid in the structure, and then dried to finally obtain a magnetic super solid acid.

[0091] The characterization results are similar to those of Example 1.

[0092] Example 3

[0093] Depend on Figure 1 The process of preparing a magnetic super-strong solid acid using organic solvent lignin as raw material includes: 1) cleaning and removing impurities; 2) carboxymethylation; 3) lignin / Fe2O3 magnetic composite material; 4) sulfonation, and the specific operations are as follows:

[0094] 1) Cleaning and removing impurities

[0095] In this implementation case, homemade softwood organic solvent lignin obtained by using ethanol was selected, and after being immersed in 80°C water and stirred for 1 hour, solid-liquid separation and drying were performed.

[0096] 2) Carboxymethylation

[0097] After mixing 10g of lignin with 40ml of deionized water, add 0.1g of sodium hydroxide and knead at room temperature for 1 hour until completely mixed; then heat to 80°C, add 0.29g of sodium chloroacetate and react for 4 hours; after the reaction, add 100ml of water to dilute the system, and adjust the system to acidity with a dilute hydrochloric acid solution; collect the acid precipitated lignin, dry and grind the product to obtain carboxylated lignin.

[0098] 3) Lignin / Fe2O3 magnetic composite material

[0099] 10 g of carboxymethylated lignin was dispersed in 100 ml of deionized water and ultrasonicated for 30 minutes. The pH value of the solution was adjusted to 9–10 with 30% ammonia solution to completely dissolve the lignin. Then 2 g of FeCl3·6H2O and 0.79 g of FeCl2·4H2O were dissolved in water. 3+ / Fe 2+ The salt solution is slowly added to the lignin alkaline solution and stirred continuously; then the system is heated to 80°C, and 2.38g of 80% hydrazine hydrate is slowly added, and after stirring and reacting for 4 hours, the resulting black solution is cooled to room temperature; the pH of the solution is adjusted to acidity with a dilute hydrochloric acid solution, and the precipitated solid is filtered, washed, dried, and ground to obtain a lignin / Fe2O3 magnetic composite material;

[0100] 4) Sulfonation

[0101] The obtained 10g lignin / Fe2O3 magnetic composite material is dispersed in a mixed solution system of 100ml ethanol and 10ml water; then 2g 4-diazobenzenesulfonate is added, the temperature is controlled at 80°C, and the reaction is stirred for 2 hours; the separated product is washed with deionized water until the pH value is about 6 to ensure that there is no free acid in the structure, and then dried to finally obtain a magnetic super solid acid.

[0102] The characterization results are similar to those of Example 1.

[0103] Embodiment 4:

[0104] A method for preparing a magnetic super-strong solid acid using kraft lignin as a raw material, wherein the preparation method and specific operation thereof are the same as those of Example 1, except that the raw material is changed to kraft lignin.

[0105] The characterization results are similar to those of Example 1.

[0106] Embodiment 5:

[0107] A method for preparing a magnetic super-strong solid acid using kraft lignin as a raw material, wherein the preparation method and specific operation thereof are the same as those of Example 4, except that the alkali agent is changed to sodium carbonate.

[0108] The characterization results are similar to those of Example 1.

[0109] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A lignin-based magnetic super-strong solid acid, characterized in that: The lignin-based magnetic super-strong solid acid is obtained by subjecting lignin to carboxylation modification, magnetic material compounding and sulfonation modification.

2. The lignin-based magnetic super solid acid according to claim 1, characterized in that: The acidic site content of the lignin-based magnetic super-strong solid acid is 0.5-2 mmol / g.

3. A method for preparing the lignin-based magnetic super-strong solid acid according to any one of claims 1 or 2, characterized in that: The following steps are involved: (1) mixing lignin, an alkaline substance, a carboxylation agent, and water, and performing reaction I to obtain carboxylated lignin; (2) mixing the carboxylated lignin obtained in (1), the magnetic material precursor, hydrazine, and water, and performing reaction II to obtain a composite material; (3) The composite material obtained in (2), a sulfonating agent, an alcohol and water are mixed to perform reaction III to obtain the lignin-based magnetic super-strong solid acid.

4. The preparation method according to claim 3, characterized in that: (1) The lignin is selected from at least one of alkali lignin, kraft lignin, enzymatic lignin, and organic solvent lignin; The alkaline substance is selected from at least one of sodium hydroxide, calcium hydroxide, sodium carbonate and sodium bicarbonate; The carboxylation agent is selected from sodium chloroacetate, sodium chloropropionate, 2,2,6,6-tetramethylpiperidine-1-oxide, etc. The mass of the alkaline substance is 1 to 5 wt% of the mass of the lignin; The molar ratio of the alkaline substance to the carboxylation agent is 1:1 to 3; The solid-liquid ratio of the lignin to the water is 1:4-10 g / ml.

5. The preparation method according to claim 3, characterized in that: The temperature of the reaction I is 60-80°C; The reaction time is 2 to 4 hours.

6. The preparation method according to claim 3, characterized in that: (2) The magnetic material precursor is selected from at least one of ferric chloride and ferrous chloride; The solid-liquid ratio of the carboxylated lignin to the water is 1:100-125 g / ml; The usage ratio of the carboxylated lignin to the magnetic material precursor is 99-199:1; The usage ratio of the hydrazine to the carboxylated lignin is 1 to 10 wt %.

7. The preparation method according to claim 3, characterized in that: The temperature of the reaction II is 60-90°C; The time of the reaction II is 2 to 6 hours.

8. The preparation method according to claim 3, characterized in that: (3) The sulfonating agent is selected from 4-diazobenzenesulfonate and concentrated sulfuric acid; The alcohol is selected from ethanol; The volume ratio of the water to the alcohol is 1:10-20; The mass ratio of the sulfonating agent to the composite material is 10:1 to 5:2; The ratio of the total mass of the sulfonating agent and the composite material to the total volume of the alcohol and the water is 1:10-100 g / ml.

9. The preparation method according to claim 3, characterized in that: The temperature of the reaction III is 50-80°C; The time of the reaction III is 2 to 6 hours.

10. Use of the lignin-based magnetic super-strong solid acid according to any one of claims 1 or 2, characterized in that: It can be quickly separated and recycled by magnets.

Citation Information

Patent Citations

  • Preparation method of xylogen-based magnetic solid acid catalyst

    CN104624207A

  • Magnetic carbon-based solid acid catalyst with core-shell structure and preparation method of magnetic carbon-based solid acid catalyst, as well as application in lignocelluloses saccharification process

    CN106215951A

  • Method for preparing glucose by catalyzing cellulose hydrolysis through magnetic solid acid

    CN109777896A

  • Preparation method and application of biomass straw-based magnetic solid acid catalyst

    CN112844409A

  • Preparation method of magnetic solid acid and application of magnetic solid acid in biomass hydrolysis

    CN115475656A